Perancangan Sistem Informasi Geografis Lokasi Bengkel Sepeda Dengan Model Waterfall Berbasis Web di Kota Tangerang Selatan - Rama Kusuma; Kussigit Santosa (CV. Multi Kreasi Media, 2022)
The development of technology in the current era of globalization is very fast. Information technology has become a very commonplace and a necessity in all aspects of human life in the provision and provision of information. At this time, information is limited to the general public and cyclists who need information about an lokasi, especially those living in South Tangerang City in seeking information about the location of the bicycle workshops. With these problems, the authors offer an Information System Design. The system that the author is trying to make uses the PHP programming language using MySQL as the database. The method used in developing the waterfall system (the waterfall method) is a classical model that is systematic, sequential in building software. The results of the research are a web-based bicycle workshop location geographic information system, which can provide information on the location of bicycle workshops, bicycle repair products and bicycle events. Thus, it can be concluded that the system functionality runs well by 80%, the system interface is quite easy to use, and the system is relatively useful for 70% of the blackbox test results. Keywords : Workshop, PHP, MySQL, Information System.